AN INVESTIGATION OF THE ROLE OF SOCIAL ACCEPTANCE IN THE CONTEXT OF WOMEN'S IDENTITY IN BERTOLT BRECHT'S STORY 'THE UNWURDIGE GRYZIN' - Jahel, Roshan Lal; Prakash, Om (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the role of women's identity and social acceptance in Bertolt Brecht's work 'The Unwurdige Gryzin'. This story depicts the last two years of an old woman's life, where she struggles for her freedom and identity. Brecht has effectively highlighted the conflict between a woman's personal freedom and social acceptance. This story combines feminism and psychological aspects and raises the question whether women empowerment is possible without a change in society's attitude. Brecht has criticized the structures and traditional beliefs of society, which deprive women of their rights and freedom. Through this work, Brecht shows that women empowerment is impossible without a change in the attitude of society.